Seasonal changes in biomass yield, nutrient intake and its utilization by sheep maintained on public range land - Sankhyan, S K; Shinde, A K; Karim, S A (The Indian Journal of Animal Sciences, 2012)
Seasonal changes in biomass yield of pasture and nutrient utilization pattem of sheep maintained round the year on village community grazing land (CGL) was assessed. The biomass yield of the CGL was similar in the 3 seasons (1.54q DM/ha). Animal preferred Cenchrus catherticus and Eleucine indica during rainy season whereas during winter the preference for C. catherticus increased while that of Elucine indica decreased. The CP of random pasture vegetation was 10.5% in monsoon which declined to 8.4 and 4.0% in winter and summer, respectively. with concomitant increase in cell wall constituents during the period. The CP of mouth grab samples was, however, 11.5% in monsoon and 10.0 and 7.8%, respectively, in winter and summer. The DMI of sheep decreased from monsoon (2.1 % BW) to winter (1.8% BW) and summer (1 .6% BW), while corresponding DCP intake showed significant reduction in. summer ( 15 g/head/day) compared to winter (31.1 g/head/day) and monsoon (45. 1 g/head/day). Progressive increase in maturity and lignification of plant species was reflected in gradual decline of digestibility of DM, CP, NDF, ADF, hemicellulose and cellulose from monsoon to winter and summer. It is concluded that DMI and nutrient utilization progressively decreased from monsoon to winter and summer. The DCP intake was adequate in monsoon and winter while it was grossly inadequate in summer.